The Impact of Non-Performing Financing and Liquidity Risk on Return on Asset at PT Bank Central Asia Syariah - Nurzianti, Rahma; MA, Rosdaniah; Paraswati, Melisa (Jurnal Akuntansi Muhammadiyah (JAM), 2024)
This research aims to find out how the influence Non Performing Financing (NPF) and Liquidity Risk partially and simultaneously on Profitability at PT BCA Syariah (Period 2015-2022)”. The research method used is a quantitative method. This research uses secondary data obtained from www.bcasyariah.co.id, the sample data is the quarterly financial report of PT BCA Syariah for the period 2015-2022, with data taken for 8 years with The quarterly method is the latest data or this period has not been studied by many people. The analysis techniques used are classical assumption tests, multiple linear regression analysis and hypothesis testing with a significance level of 0.05%. The results of this research partially show that NPF does not have a significant effect on profitability at PT BCA Syariah. The partial Liquidity Risk (FDR) variable has no significant effect on Profitability. Meanwhile, simultaneously NPF and Liquidity Risk (FDR) have a significant effect on PT BCA Syariah's profitability. This is quite interesting if you look at the coefficient values of the two variables, namely NPF and FDR, which influence the profitability of PT BCA Syariah.